2018
DOI: 10.18011/bioeng2018v12n2p132-143
|View full text |Cite
|
Sign up to set email alerts
|

APROVEITAMENTO DO LODO DE ESGOTO E DA CASCA DE PALMITO NA PRODUÇÃO DE MUDAS DE Lantana câmara

Abstract: O uso do lodo de esgoto na agricultura tem se mostrado cada vez mais promissor, principalmente no que se refere ao cultivo de florestais e plantas ornamentais. Objetivou-se avaliar a viabilidade da produção de mudas de Lantana camara, planta ornamental amplamente produzida no Vale do Ribeira – São Paulo, utilizando lodo de esgoto compostado com casca da pupunha, lodo caleado, ou em combinações com outros componentes estruturantes, como esterco bovino, solo e casca de arroz carbonizada. Para tanto, foram formu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
1
0
1
Order By: Relevance
“…Thus, as there was no complementary fertilization for any of the treatments, the nutrients contained in the treatment composed only of subsoil were not adequate enough to help the growth of the seedlings, resulting in seedlings with undesirable characteristics. For the ornamental species Lantana camara L., the authors Barone et al (2018) also observed that sewage sludge, used pure or in mixtures with pupunha bark (Bactris gasipae Kunth) positively influenced the height growth of seedlings and attributed these findings to the high contents of nutrients and organic matter in the composition of these substrates. Additionally, Pêgo et al (2019) when evaluating the quality of Zinnia elegans seedlings produced in alternative substrates obtained greater seedling height with the substrate obtained by composting agricultural waste and, Barroso et al (2020) when producing seedlings of the same species in substrates based on carnauba bagasse observed an increase in height with the increase in the proportion of compost in the substrates.…”
Section: Resultsmentioning
confidence: 96%
“…Thus, as there was no complementary fertilization for any of the treatments, the nutrients contained in the treatment composed only of subsoil were not adequate enough to help the growth of the seedlings, resulting in seedlings with undesirable characteristics. For the ornamental species Lantana camara L., the authors Barone et al (2018) also observed that sewage sludge, used pure or in mixtures with pupunha bark (Bactris gasipae Kunth) positively influenced the height growth of seedlings and attributed these findings to the high contents of nutrients and organic matter in the composition of these substrates. Additionally, Pêgo et al (2019) when evaluating the quality of Zinnia elegans seedlings produced in alternative substrates obtained greater seedling height with the substrate obtained by composting agricultural waste and, Barroso et al (2020) when producing seedlings of the same species in substrates based on carnauba bagasse observed an increase in height with the increase in the proportion of compost in the substrates.…”
Section: Resultsmentioning
confidence: 96%
“…Muitos estudos têm mostrado resultados positivos do uso do lodo de esgoto como fertilizante orgânico, os resultados mostram que houve aumentos na produção de massa seca (BARONE et al, 2018), área foliar (SIQUEIRA et al, 2019) e índices fisiológicos (BERTOLAZI et al, 2017).…”
Section: Introductionunclassified